Beginning with the end in mind: Implementing backward design to improve sports injury rehabilitation practices - Chia, L.; Taylor, D.; Pappas, E.; Hegedus, E. J.; Michener, L. A. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Current injury-specific return-to-performance rehabilitation programs are not comprehensive, lack intensity, and need better tailoring to the demands of sport. The vast number of rehabilitation and return to sport protocols also reflects a lack of consensus about what the best program looks like, which hinders beginning practitioners from implementing best practices across the spectrum of injuries and sports. Backward design, which has underpinnings in educational research, can facilitate implementation by encouraging practitioners to begin with the end in mind before logically and intentionally working backwards to design transferable and context-specific rehabilitation plans that improve sports injury rehabilitation practices. We discuss and illustrate using case examples how clinicians can apply backward design in best practice sports injury rehabilitation.